(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Short-lived fruits like Mango (Mangifera indica) are to be subjected to cooling after reaping to increase their storage life. Hydro cooling method is found to achieve faster heat transfer. In the current study, Response surface methodology was used to search for the foremost storage conditions of the hydro-cooling system to extend the shelf life of mango coated with antimicrobial extract (Neem leaf extract). The cooling rate was most affected by cooling chamber temperature (13 ̊C,16 ̊C and 22 ̊C), fruit size (0.11, 0.13 and 0.17 m) and water flow rate (0.83 l/hr, 1.16 l/hr and 4.16 l/hr). The most suitable conditions to store mango fruits under hydro cooling were determined as cooling chamber temperature (13 ̊C), fruit size (0.11 m) and water flow rate (4.16 l/hr). The shelf life for mango was prolonged to 32 days. Percentage Loss in Weight for the control sample was 9.38% within 8 days of storage whereas for the cooled sample it was 4.19- 8.26 % for 32 days of storage also, Total Soluble Solids was 16.33 -24.00 ̊Brix the for control and cooled sample it was 16.33-25.00 ̊Brix for 8 and 32 days of storage. Time taken for Cooling was 55, 45 and 40 mins for 0.17m, 0.13m, and 0.11m size fruits respectively.